Chemical and mechanistic analysis of photodynamic inhibition of Alzheimer's β-amyloid aggregation. Issue 8 (11th January 2019) - Ahn, Minkoo; Lee, Byung Il; Chia, Sean; Habchi, Johnny; Kumita, Janet R.; Vendruscolo, Michele; Dobson, Christopher M.; Park, Chan Beum
Abstract : Inhibition of Aβ42 aggregation by photoexcited thioflavin T that generates singlet oxygen to oxidize monomeric Aβ42 . Abstract : The self-assembly of the beta-amyloid peptide (Aβ) into amyloid aggregates is a central phenomenon associated with Alzheimer's disease. Here, we report chemical modifications of key amino acid residues of Aβ42 (Y10, H13, H14, and M35) by photoexcited thioflavin-T (ThT), a fluorescent probe of amyloid structure. The quantitative chemical kinetics analysis shows that the oxidized monomer species does not self-assemble, nor perturb the aggregation kinetics of non-oxidized Aβ42 .